A Flow Cytometric Clonogenic Assay Reveals the Single‐Cell Potency of Doxorubicin. Issue 12 (7th September 2015) - Maass, Katie F.; Kulkarni, Chethana; Quadir, Mohiuddin A.; Hammond, Paula T.; Betts, Alison M.; Wittrup, Karl Dane
Abstract : Standard cell proliferation assays use bulk media drug concentration to ascertain the potency of chemotherapeutic drugs; however, the relevant quantity is clearly the amount of drug actually taken up by the cell. To address this discrepancy, we have developed a flow cytometric clonogenic assay to correlate the amount of drug in a single cell with the cell's ability to proliferate using a cell tracing dye and doxorubicin, a naturally fluorescent chemotherapeutic drug. By varying doxorubicin concentration in the media, length of treatment time, and treatment with verapamil, an efflux pump inhibitor, we introduced 10 5 –10 10 doxorubicin molecules per cell; then used a dye‐dilution assay to simultaneously assess the number of cell divisions. We find that a cell's ability to proliferate is a surprisingly conserved function of the number of intracellular doxorubicin molecules, resulting in single‐cell IC50 values of 4–12 million intracellular doxorubicin molecules. The developed assay is a straightforward method for understanding a drug's single‐cell potency and can be used for any fluorescent or fluorescently labeled drug, including nanoparticles or antibody–drug conjugates. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4409–4416, 2015